Information and Communications in the Chinese Countryside : A Study of Three Provinces - Minges, Michael (Washington, DC: World Bank, 2014)
The report first summarizes the key findings from the following three studies in three provinces (Guizhou, Jilin, Shandong): (a) a demand survey to assess rural ICT access and attitudes; (b) a library study including scoping the status of ICT use in rural libraries; and (c) a limited impact evaluation to examine how ICT interventions have affected rural uers. Then the report addresses the challenges and policy recommendations of ICT use in the Chinese Countryside.